TRANSFORMASI PENGGUNAAN JILBAB OLEH ARTIS INDONESIA (2001-2017) - Alfakhruji, Syahid Wizdan; Sulasman; Lestari, Fathia (Jazirah: Jurnal Peradaban dan Kebudayaan, 2026)
This research analyzes the transformation of hijab usage among Indonesian celebrities from 2001 to 2017. The primary issue addressed is the deconstruction of the hijab's image, which was initially perceived as rigid and a hindrance to professionalism during the New Order era, into a modern and emancipatory popular identity through the strategic role of public figures. The objective of this study is to map the phases of changes in hijab aesthetics and identify the driving factors that transformed this religious attribute into a symbol of international achievement. The methodology employed is the historical research method, encompassing four stages: heuristics through the collection of primary sources in the form of contemporary media clippings (Pikiran Rakyat, Galamedia) and oral sources (interview documentation), source criticism, interpretation, and historiography. The analysis was conducted using Homi K. Bhabha’s theory of cultural hybridity to observe the emergence of a "Third Space" as a realm of negotiation between spiritual values and the aesthetics of the entertainment industry. The results indicate that the transformation was initiated by the pioneering actions of celebrities such as Inneke Koesherawati and Nella Regar in 2001, who navigated their identities amidst professional career risks. This development culminated in 2017 with Dian Pelangi’s achievements at New York Fashion Week, which historically marked the phase of the hijab's establishment as a globally recognized popular identity. This research concludes that celebrities act as agents of hybridity who create a 'Third Space,' a negotiation zone that successfully converges popular culture with religious values. The presence of this space destabilizes old narratives regarding the hijab, transforming it from marginal attire into a symbol of progress and professionalism for modern Muslim women in Indonesia’s public sphere.